Analysis of the spatio-temporal characteristics and driving forces of greenness in mega urban agglomerations in China - Shaoyu Wang; Dongmei Yan; Yayang Lu; Wanrong Wu; Ying Sun; Zhe Zhang (Ecological Indicators)
Timely monitoring of greenness dynamics in urban agglomerations and analyzing their driving factors are important for sustainable development. However, current research on vegetation greenness at the scale of urban agglomerations remains limited. This study examines the greenness dynamics and its driving factors in China’s four major urban agglomerations Beijing–Tianjin–Hebei (BTH), Yangtze River Delta (YRD), Pearl River Delta (PRD), Chengdu–Chongqing (CC) at a 30-meter spatial resolution over a long period (2000–2023). The use of an innovative integrated approach, combining the Gap Filling and Savitzky–Golay filtering (GF-SG) method, pixel dichotomy model, spatiotemporal dynamic analysis and geographical detector, provides a more comprehensive understanding of greenness dynamics in urban agglomerations. The results indicate several key points: 1.The proportion of areas where vegetation greenness increased (27.69 %, 14.10 %, 31.56 %, 23.09 %) is consistently larger than the proportion of areas where greenness decreased (4.3 %, 6.78 %, 5.11 %, 1.62 %) within BTH, YRD, PRD, CC. Greenness is dramatically increasing in all urban centers, but significantly decreasing at the edges of urban expansion; 2. Land cover conversions emerged as the dominant driver of greenness changes (the highest Q-value is 0.5743), which indicates that land cover conversions play a greater role than natural factors. 3. The expansion of urban land and ecological land restoration explain the main reasons for the decrease and increase in greenness. Meanwhile, there are differences in the primary land cover conversions corresponding to the greenness changes among the four urban agglomerations. These findings not only contribute to understanding urban greenness dynamics but also offer a new perspective on the role of land cover conversions in shaping vegetation patterns.